COVID-19 and Intestinal Ischemia: A Multicenter Case Series - Sarkardeh, Maryam; Meftah, Elahe; Mohammadzadeh, Narjes; Koushki, Javad; Sadrzadeh, Zahra (Frontiers in Medicine, 2022)
Introduction: Gastrointestinal symptoms are common among COVID-19 patients. Although gastrointestinal involvements are mostly benign, they rarely indicate a severe pathology like intestinal ischemia. The present case series describes 21 patients with bowel ischemia, necrosis, or perforation. Methods: The present case series was conducted from April 2020 to February 2022 in the surgical wards of two Iranian hospitals. We retrospectively included adult patients with concomitant COVID-19 and intestinal ischemia. Primary outcomes were defined as the length of stay and survival. Results: Twenty-four patients with a median age of 61.5 years were included in the study. Sixteen (67%) patients were male, and 13 (54%) were without any comorbidities. Macrovascular mesenteric ischemia was not identified in 21 patients (87.5%). Gastrointestinal manifestations appeared on the median of seven days (range 2 – 21) after the diagnosis of COVID-19, with the most common symptom being abdominal pain. All the patients had a significantly elevated C-Reactive Protein prior to surgery, ranging from 68 to 362. D-dimer was measured in eight patients and was significantly elevated, ranging from 1878 to over 5000 ng/mL. One patient was managed conservatively due to a good clinical condition. Except for one patient with angioinvasive mucormycosis and one other with leukocytoclastic vasculitis, pathologic evaluation revealed general features of intestinal necrosis, including ulcer, hemorrhage, necrosis, neutrophilic infiltration (in seven patients), neutrophilic abscess (in four patients), and edema. Bowel necrosis accompanied mortality of 15 (62.5%) patients and a median of 6.5 days of hospital stay. Conclusion: Intestinal ischemia in COVID-19 patients is associated with a high mortality rate. Further research is needed to elucidate the dynamics of intestinal ischemia in the setting of COVID-19.